Governing the landscape: potential and challenges of integrated approaches to landscape sustainability in Indonesia - Riggs, R.A.; Achdiawan, R.; Nawir, A.A.; Boedhihartono, Agni K.; Kastanya, A.; Langston, James D.; Priyadi, H.; Ruíz Pérez, M.; Sayer, J.; Tjiu, A. (Springer, 2021)
In recent years, landscape sustainability, the maintenance and improvement of biodiversity, ecosystem services, and human well-being in landscapes, has become a core objective of conservation initiatives. Yet efforts to promote sustainability often conflict with other landscape objectives. Globally, integrated landscape approaches have emerged as desirable processes for reconciling these conflicts. Integrated landscape approaches seek to foster improvements in landscape-scale governance to meet sustainability objectives. As scientific and political support for these new landscape approaches continues to advance internationally, there is a need to learn from the processes, constraints, and opportunities. We seek to enrich understandings of landscape approaches and their contributions to governance and sustainability through conserving biodiversity and maintaining ecosystem services. Focusing on eight case studies at different stages of development in Indonesia, we explore how practitioners influence landscape sustainability through integrated approaches. We used questionnaires and literature to collect information on objectives, attributes and challenges of landscapes approaches. We find landscape approaches in Indonesia closely reflect guidance principles. Emerging lessons from landscapes include adapting strategies to local priorities for inclusive problem-framing and engaging in nested learning systems. Aligning landscape actions with policy for coherent governance across scales remains a key challenge. Creating and maintaining governance that supports landscape sustainability is a core principle of landscape approaches. Establishing institutional arrangements for landscape sustainability will require working across legislative and political boundaries for coordinated action. We highlight the need to document and measure impact, and the potential for future learning from landscape sustainability science.